2022
DOI: 10.1093/rheumatology/keac152
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the MUC5B promoter variant with timing of interstitial lung disease and rheumatoid arthritis onset

Abstract: Objective To investigate the associations of the common MUC5B promoter variant with timing of RA-associated interstitial lung disease (RA-ILD) and RA onset. Methods We identified patients with RA meeting 2010 ACR/EULAR criteria and available genotype information in the Mass General Brigham Biobank, a multi-hospital biospecimen and clinical data collection research study. We determined RA-ILD presence by reviewing all RA patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…20 Recently, the MUC5B variant was also identified as a risk factor for early onset RA-ILD. 21 Wheeler et al found that MUC5B polymorphisms were less frequent in African Americans but carried a stronger association with RA-ILD. 22 In addition, environmental particulate and cigarette smoke exposure may vary by country of origin and may increase RA-ILD risk.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recently, the MUC5B variant was also identified as a risk factor for early onset RA-ILD. 21 Wheeler et al found that MUC5B polymorphisms were less frequent in African Americans but carried a stronger association with RA-ILD. 22 In addition, environmental particulate and cigarette smoke exposure may vary by country of origin and may increase RA-ILD risk.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 may be a trigger for postfibrotic lung disease in some, and RA patients are particularly susceptible to ILD [ 65 ]. This may be in part due to the MUC5B promoter variant, the strongest genetic risk factor for RA-ILD [ 66 , 67 ] that increases risk for pulmonary fibrosis after infection resolution. It is also possible that PASC could modify the RA disease course by inducing autoimmunity and promoting systemic inflammation [ 68 70 ].…”
Section: Postacute Sequelae Of Covid-19mentioning
confidence: 99%
“…The CTD group included 70 pSS, 64 SSc, and 34 PM/DM cases. Among these CTD subgroups, ILD scores were distributed as follows: 0 (n=30), 1 (10), 2 (15), and 3 (15) in pSS; 0 (15), 1 (10), 2 (15), and 3 (24) in SSc; and 0 (7), 1 (3), 2 (11), and 3 (13) in PM/ DM. Demographic and CTD characteristics and autoantibody detection results of patients with pSS, SSc, and PM/DM are listed in Table 1, most of which were not substantially different among the distinct ILD severity scores.…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
“…The pathophysiology of CTD-ILD is unclear but genetic factors are thought to play an essential role in its development ( 8 ). Previous studies have demonstrated a strong relationship between ILDs and single nucleotide polymorphisms (SNPs) in the promoter regions of mucin 5B (MUC5B) ( 7 , 9 11 ) and mucin 5AC (MUC5AC) ( 12 ). MUC5AC and MUC5B, which account for approximately 90% of the mucoproteins ( 13 ), play a crucial role in the respiratory mucosal defense arsenal.…”
Section: Introductionmentioning
confidence: 99%